Meanings of abstract art : between nature and theory - Crowther, Paul.; Wünsche, Isabel (New York : Routledge, 2012)
"This book explores the relation of abstract art to nature. Traditional picturing and sculpture are based on conventions of resemblance between the work and that which it is a representation "of". Abstract works, in contrast, adopt alternative modes of visual representation, or break down and reconfigure the mimetic conventions of pictorial art and sculpture. Obviously this means that abstract art takes many different forms. However, this diversity should not mask some key structural features; these center on two basic relations to nature (understanding nature in the broadest sense to comprise the world of recognisable objects, creatures, organisms, processes, and states of affairs). The first involves abstracting from nature, to give selected aspects of it a new and extremely unfamiliar appearance. The second involves abstract art as the affirmation of a relatively unconstrained natural creativity that issues in new, autonomous forms that are not constrained by mimetic conventions. (Such creativity is often attributed to the power of the unconscious.)The book contains three categories of essays: 1) those on classical modernism (Mondrian, Malevich, Kandinsky, Arp, early American abstraction), 2) those on post-war abstraction (Pollock, Still, Newman, Smithson, Noguchi, Arte Povera, Michaux, postmodern developments), and 3) those of a broader art historical and philosophical scope"--
Includes bibliographical references (pages [283]-284) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Art, Modern -- 20th century -- Philosophy; Art, Abstract; Nature (Aesthetics); Electronic books